FACTOR RESEARCH OF PRIME COST OF INTERNATIONAL ROAD TRANSPORTATION OF PARTY CARGO - Ширяєва Світлана Володимирівна; Свірін Дмитро Олександрович (World Science, 2020)
One of the important tasks to be solved by carriers and freight forwarders in the organization of international road transportation of party cargoes is the choice of effective methods of cargo transportation. For this purpose it is expedient to estimate each method on criteria of efficiency of the international road transportations of party cargoes (time, financial, etc.). A very important financial criterion is the prime cost of 1 km of the vehicle mileage during the international road transportation of party cargoes. The influence of factors on it, such as: mileage of vehicles, operating costs for international road transportation of party goods, the volume of the consignment of goods transported. Factor analysis was performed by different methods: multiple regression, nonlinear multiple regression and neural networks. According to the results of research, we can conclude that the smallest balances in the prediction of neural networks, because they are self-improving and give a more accurate result.